Methods of Statistical Sampling in the Process of Auditing - Mackevičius, Jonas; Valkauskas, Romualdas (Ekonomika, 2007)
Sampling is one of the most important audit procedures. However, data research on how to use sampling methods in auditing are scarre. In the literature on audit, the same as in the international and national audit standards, sampling methods and their use in the process of auditing are analysed very closely, without differentiating among the cases and circumstances when to use them, what is the effectiveness of method, the level of risk, etc.The purpose of the article was to perform an analysis of the statistical and nonstatistical usage of the sampling methods in the Lithuanian audit system and to prepare a methodology of the statistical use of the method.The analysis allowed to formulate the following conclusions:1. The nonstatistical sampling method is usually used in auditing small enterprises unable to check the large amount of household operations which usually are the most difficult and the most significant.2. The nonstatistical sampling method is the most effective when the audit in the company is performed not in the first year and the auditor uses information gathered earlier.3. The advantages of the statistical sampling method are more significant than of the nonstatistical method. The statistical sampling method accurately describes the size of a sample, the evaluation of the test results is more accurate, it determines the size of tolerable mistakes, guarantees a more objective evaluation of sample risk. The method of statistical sampling guarantees a high quality of results and there fore is more often used in the audit practice all over the world.4. Which - statistical and nonstatistical sampling method to use depends on several reasons: auditor’s professional competence, practice, the size of the company and its activity, the size of audited objects and the in complexity, the circumstances during audit, etc. International audit practice confirmed that the auditor, before choosing the statistical or nonstatistical sampling method, first should evaluate certain circumstances, and whether these methods will bring reliable and sufficient evidence, and to evaluate the cost of these methods.5. The use of the statistical sampling method is limited by absence of audit methodology. Auditors know not enough about the statistical sampling methods and how to use them during auditing certain objects.It is recommended in audit processes to use three steps of the statistical sampling method: 1) preparation for research, 2) control performed sampling and obtained results, 3) analysis and usage of the results. 10 each step, certain tasks are performed. These tasks allow obtaining a sufficient and reliable audit evidence.Scientific research of the use of sampling methods should be continued. It is most important to evaluate the auditor’s opinion depending on his I her qualification and age: it is important to determine whether unqualified and young auditors use the statistical method and more qualified and older auditors prefer the nonstatistical method.